Pro SQL Database for Windows Azure SQL Server in the Cloud - Klein, Scott; Roggero, Herve (Apress : Imprint: Apress, 2012)
Pro SQL Database for Windows Azure, 2nd Edition shows how to create enterprise-level database deployments without the usual investment in datacenter and other infrastructure. Take advantage instead of Microsoft's worldwide backbone for cloud computing that delivers all the power of SQL Server in the form of the cloud-based SQL Database for Windows Azure. You can create and deploy a database in mere minutes that is accessible worldwide and takes advantage of SQL Database's high-availability features to protect your data while ensuring 99.9% uptime. SQL Azure is ideally suited for startups, who can benefit from instant access to a robust and secure web-accessible database platform for use in rapidly deploying new products to market. SQL Azure is also ideal for small and mid-sized businesses, giving them the same ability to deploy SQL Server as any large enterprise, but without the management overhead. Even large enterprises find SQL Azure useful in creating failover environments, development environments, extra capacity to handle surges in demand, and more. Pro SQL Database for Windows Azure covers the very latest in Microsoft's fast-moving, cloud platform, showing how to program and administer it in a variety of cloud computing scenarios. You'll learn to program SQL Azure from ASP.NET, from WinForms, and from SQL Reporting Services. You'll learn to manage the platform by planning for scalability, troubleshooting performance issues, and implementing strong security. You'll learn the unique aspects of SQL Azure such as sharding and federation support that combine to place SQL Azure a step above and ahead of the competiton. Shows how to use SQL Azure from classic Windows applications, ASP.NET and Windows Communication Foundation Covers management, performance, scalability, and troubleshooting Addresses the all-important issue of securing your data Helps you properly design for high-performance in a cloud environment Helps you adopt the new Federations feature in SQL Azure.